Preliminary study on association of EDNRB gene with heterochromia iridis in cats (Felis catus) - Siriwadee Chomdej (2018)
© 2018, Veteriner Fakultesi Dergisi. All rights reserved. This study conducted an investigation on three exons of the endothelin receptor type B (EDNRB) gene of Thai odd-eyed cats to find out the association between the variations in the gene and heterochromia iridis. DNA sequencing analysis was performed on 11 odd-eyed cats compared to 11 normal-eyed cats. Seven variations were found across the studied region (XM_003980457.2: c.610A>G, c.820+40C>T, c.821-14C>T, c.916A>G, c.1025+36G>T, c.1025+69A>T, and c.1025+138C>T) with two of them (c.610A>G and c.916A>G) causing amino acid changes (P.Asn128Ser and P.Val230Ala). There was no statistical association between the variations near the three exons of EDNRB and feline heterochromia iridis (chi-square test, P-value >0.05).